Improving the delivery ratio in vehicular delay‐tolerant network using customized binary particle swarm optimization‐based optimized throwbox deployment. (31st October 2022) - Chourasia, Vishakha; Pandey, Sudhakar; Chaurasiya, Rahul; Kumar, Sanjay
Summary: Vehicular delay tolerant networks (VDTNs) suffer due to insufficient connection opportunities in sparse infrastructure. The sparsity of the network results in poor delivery ratio (DR). Deployment of additional small nodes named throwbox increases the contact opportunities, resulting in improved performance in terms of DR. However, randomly deployed throwboxes do not provide optimum results. Therefore, this article proposes the throwbox deployment as an optimization problem. Customized binary particle swarm optimization‐based optimization method is employed to solve the problem. With the objective of maximizing the DR, the method optimize the placement of k k ‐ throwboxes in the network. The performance of the proposed methods is tested and compared by simulating a VDTN model in opportunistic network environment simulator. The optimization framework was implemented in Matlab. Exhaustive experiments were carried out by varying the number of throwboxes ( k k ). A statistical comparison of the results with the existing throwbox deployment methods validates the effectiveness of the proposed optimization‐based approach. The article also presents an analysis for choice of value of k k for a desired network performance.